Impact of Extraction the Cause in Financial Transactions: A Comparative analytical Study - Alhosean, Ahmad Hamood (Journal of Islamic Sciences, 2021)
The study aimed at showing practical impact which results from the process of extracting the cause in the matters of financial transactions. The researcher used for that the comparative analytical approach , where he turned to follow proofs of the very specific intentional financial transaction ; then, these proofs through abstract procedural and methodological tracks, to inspect the latent causes behind permission or prohibition of these transactions , in order these inferred doctrinal provisions to be adopted at the same course in relation to other transactions that take part with the same ones that their causes have been extracted. Undoubtedly, the type of transactions from which the researcher has taken the subject of his research that its cause is undiscussed, or what texts permit a decision without minimum sign to their cause; where the researcher studied the transaction of a man who purchases what he doesn't have, relying on proofs in this connection; then , he had inferred the cause of this transaction and extracted it , to arrive at the doctrinal impact arising from this extraction , i.e. giving the decision of this transaction itself to other transactions participating with it the cause as: sale of unawareness , sale before receiving , sale of non- existent , or there is not ability to deliver; and between unacceptability to include other transaction within the same arrangement , since the cause is different ; and an instance of that matter is giving back female sheep with a measure equals to the duration the purchaser makes benefit from the existence of this animal at his barn; and after extracting this cause of the matter , the researcher could establish a law of doctrinal impairments.
Keywords: Cause; Extraction the Cause; Financial Transactions; the sheep which its udder is tied